Postmortem assessment of thalamic nuclear volumes in subjects with schizophrenia - Byne, William; Buchsbaum, Monte S; Mattiace, Linda A; Hazlett, Erin A; Kemether, Eileen; Elhakem, Sharif L; Purohit, Dushyant P; Haroutunian, Vahram; Jones, Liesl (The American journal of psychiatry, 2002)
The authors assessed schizophrenia-associated changes in volume and neuronal number in the mediodorsal nucleus and the pulvinar regions of the thalamus. Right-hemisphere thalami obtained at autopsy from 14 schizophrenic and eight comparison subjects were examined. Computer-assisted morphometric techniques were used to determine volumes for the mediodorsal nucleus, pulvinar, and the anterior and centromedian nuclei as well as the parvocellular, magnocellular, and caudodorsal subdivisions of the mediodorsal nucleus. Neurons in the mediodorsal nucleus and pulvinar were counted and measured by using a stereology-based sampling strategy. Four schizophrenic and three comparison subjects had Alzheimer's type pathology, leaving 10 schizophrenic and five comparison subjects without other documented neuropathological changes. In analyses that included either the full cohort or only the subjects without Alzheimer's type pathology, volumes of the mediodorsal nucleus and pulvinar, but not the anterior or centromedian nuclei, were significantly smaller in the schizophrenic subjects. For the schizophrenic subjects, neuronal number in the mediodorsal nucleus, parvocellular subdivision, and pulvinar was significantly lower, and neuronal size in the mediodorsal nucleus, caudodorsal subdivision, and pulvinar was significantly smaller. Schizophrenia is associated with volume and neuronal changes in the mediodorsal nucleus and pulvinar, the major association nuclei of the thalamus, whereas total thalamic volume and the volumes of anterior and centromedian nuclei were not significantly altered.